(untitled) (Journal of Economic Research & Business Administration, 2017)
The main goal of this article is to consider the activity of the industrial design offices in Kazakhstan. Based on the data of JSC «National agency for technological development» the map of registered and operating Kazakhstani industrial design offices was built and the main indicators of its activity was also analyzed for the period from 2012 to 2015. The article shows that industrial design offices are an important element of innovation infrastructure, encouraging the creation of new or improved products. The concept of «industrial design office» and its main services were considered in accordance with Kazakhstani legislation. The possibility of establishing of single engineering center in the image of the Eurasian engineering center for machine tools was considered as key direction of further development of the industrial design offices in Kazakhstan.